Efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2015)
Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) were synthesized. These semi-IPN hydrogel networks can potentially serve as micro or nano reactors for entrapment of metal nanoparticles. Current methodology allows us to entrap metal nanoparticles throughout hydrogel networks via poly(aspartic acid) chains which are dispersed homogeneously in the gel matrix. The Ag-NPs were characterized by UV-vis absorption spectroscopy, transmission electronic microscopy (TEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDAX). The Ag embedded hydrogels catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 very efficiently at room temperature with good recyclability upto 3 cycles.